Sosialisasi Perpajakan Dan Pendampingan UMKM Dalam Upaya Meningkatkan Kesadaran Untuk Pelaporan Pajak Tahunan Umkm Simpang Empat Pasaman Barat - Putra, Dike Rama; Pratama, Rahmatullah; Firta, Widia (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
his service is an activity of the lecturer team at the Putra Indonesia University "YPTK" Padang to socialize the Simpang Empat Pasaman Barat . The activities provided aim to make SMEs aware of the importance of annual tax reporting. This activity was carried out as feedback from the needs analysis action (need survey) that had been carried out by the service team on several MSMEs where information was obtained that many MSMEs did not report their annual taxes. The service is carried out using 2 methods, namely direct lectures which contain explanations about taxes and the importance of tax reporting